The Role of Islamic Education Teachers in Promoting Student Discipline Through Character Based Instruction at SDN 169 Bolang, Enrekang Regency, Indonesia - Sri Bulan; Rosmiati Ramli; Djamaluddin Djamaluddin; St. Warda Hanafie Das; Amir Patintingan (CV. Gerasi Insan Nusantara, 2026)
This thesis examines the role of Islamic Religious Education (IRE) teachers in implementing character-based learning to improve students’ discipline at SDN 169 Bolang, Enrekang Regency. The study focuses on three main aspects: (1) the role of IRE teachers in applying character-based learning to enhance students’ discipline, (2) the character-based learning strategies employed by IRE teachers, and (3) efforts to overcome challenges in implementing character-based Islamic Religious Education that influence students’ disciplinary behavior. This research employed a qualitative approach with pedagogical and psychological perspectives. The study was conducted over a period of three months at SDN 169 Bolang, Enrekang Regency. Primary data sources included the school principal, Islamic Religious Education teachers, and school operators, while secondary data sources consisted of school documents, journals, articles, and other relevant references. Data were collected through observation, interviews, and documentation. Data analysis techniques involved data reduction, data presentation, and drawing conclusions. The validity of the data was ensured through credibility, transferability, dependability, and confirmability. The findings indicate that character-based learning through Islamic Religious Education at SDN 169 Bolang is effective in improving students’ discipline. Islamic Religious Education teachers play a central role as role models by integrating religious values into learning activities, implementing routine habituation, applying consistent rewards and educational consequences, and using active and reflective learning methods. Although challenges such as differences in students’ character, external environmental influences, and limited parental support were encountered, these obstacles were successfully addressed through strong collaboration among teachers, homeroom teachers, and parents, as well as through consistent and adaptive approaches. Consequently, the formation of students’ disciplinary character can be developed effectively and sustainably.